1985
DOI: 10.1002/ana.410180505
|View full text |Cite
|
Sign up to set email alerts
|

The effect of carbidopa on the pharmacokinetics of intravenously administered levodopa: The mechanism of action in the treatment of parkinsonism

Abstract: The pharmacokinetics of short and long intravenous infusions of levodopa with and without concurrent oral administration of carbidopa was studied in 9 parkinsonian patients. Carbidopa reduced by 50% both the infusion rate required to produce a clinical response and the time required for plasma clearance of levodopa. Using this value for clearance, it is estimated that carbidopa doubles the bioavailability of orally administered levodopa. Carbidopa did not alter the therapeutically effective plasma concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
1
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(79 citation statements)
references
References 19 publications
1
76
1
1
Order By: Relevance
“…Our findings in common with those of Nutt et al (1985) suggest that the pharmacokinetics in patients whose clinical response is fluctuating may be different from the traditional picture. Six out of the seven subjects in our study exhibited biphasic elimination with a rapid a phase.…”
Section: -Ome Dopasupporting
confidence: 63%
See 1 more Smart Citation
“…Our findings in common with those of Nutt et al (1985) suggest that the pharmacokinetics in patients whose clinical response is fluctuating may be different from the traditional picture. Six out of the seven subjects in our study exhibited biphasic elimination with a rapid a phase.…”
Section: -Ome Dopasupporting
confidence: 63%
“…Changes in plasma concentration are summarised in Table 4 and show a large variation between patients in pre-dose (2.3-7.7 ,ug ml-') and plateau values (3.3-7.5 ,ug ml-'), although in each patient (Birkmayer et al, 1973;Morris et al, 1976;Sasahara etal., 1980;Broe etal., 1981) that following a rapid distribution phase elimination of the drug from plasma is essentially a first order process with a relatively short elimination half-life of 0.5-1.0 h. Concurrent therapy with decarboxylase inhibitors is reported (Huebert et al, 1983) to have little effect on the half-life of levodopa, in normal volunteers and patients at an early stage of treatment although plasma concentrations increase because of reductions in the clearance and volume of distribution. A recent report however (Nutt et al, 1985) has suggested there may be a modest increase in half-life in patients on long term therapy.…”
Section: -Ome Dopamentioning
confidence: 98%
“…Indeed, correction of the Vs. for lean body mass reduced the age related differences in both studies. The protein binding of levodopa is negligible (Hinterberger & Andrew, 1972) Nutt et al, (1985) found inconsistent changes in the V of levodopa administered as an infusion (2 h or > 20 h) with and without carbidopa. Kaakkola et al (1985) reported an increase in V when the ratio of oral levodopa to carbidopa was altered from 10:1 to 4:1 (although in this case the calculation of V required assumptions regarding bioavailability).…”
Section: Study B Levodopa Plus Carbidopamentioning
confidence: 99%
“…the bioavailability was 30 % (22,35). By adding an AADC inhibitor (DDI) to every levodopa dose the levodopa available in plasma is increased by 35-80 % in human (35,49,(51)(52)(53)(54). It has been shown that the DDI carbidopa reduces this first-pass metabolism to less than 10 % of the dose absorbed (52).…”
Section: Levodopa In the Peripherymentioning
confidence: 99%